FORMULASI KUKIS SUBSTITUSI TEPUNG UBI UNGU (Ipomoea batatas L.) DENGAN JAHE MERAH DAN DAUN KELOR - Asvelia, Vinca; Seveline, . (Universitas Trilogi, 2023)
Cookies are a type of biscuit made from soft dough that has a high at content and is relatively crunch. Cookies can be functional food if ingredients that have physiological activities are added in the manufacturing process that can have a positive effect on health. Some local foods that are good for health are purple sweet potato, red ginger and moringa leaves. Sweet potato flour has higher levels of ash and fiber, carbohydrates and calories are almost the same as wheat flour. The purpose of this study was to determine the effect of adding purple sweet potato flour, red ginger powder and moringa leaf powder to the organoleptic test and chemical characteristics. Based on the results of the research, the best formulation of cookies with the highest score was F3, namely cookies with 35% purple sweet potato flour, 5% red ginger powder, and 10% moringa leaf powder with 2.9% moisture content, 3.01% ash content, 6.41% protein content, and yield 96.11%. The test results of the level of preference for cookies with the substitution of purple sweet potato flour, red ginger powder and moringa leaf powder on color, aroma, texture, aftertaste, and overall were neutral